2020
DOI: 10.1007/s00421-020-04415-4
|View full text |Cite
|
Sign up to set email alerts
|

Intra-limb and muscular coordination during walking on slopes

Abstract: Purpose Intra-limb and muscular coordination during gait are the result of the organisation of the neuromuscular system, which have been widely studied on a flat terrain. Environmental factors, such as the inclination of the terrain, is a challenge for the postural control system to maintain balance. Therefore, we hypothesised that the central nervous system flexibly modifies its control strategies during locomotion on slopes. Methods Ten subjects walked on an inclined treadmill at different slopes (from − 9° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 78 publications
3
24
0
Order By: Relevance
“…At the same speed, a similar set of lower limb muscle synergies was extracted during slope walking 23 , 24 , walking with Nordic poles 30 , and walking on an uneven surface 41 as that during normal walking. Similar to these previous studies, our results also showed the similarity of the extracted muscle synergies between land and water walking at the same speed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same speed, a similar set of lower limb muscle synergies was extracted during slope walking 23 , 24 , walking with Nordic poles 30 , and walking on an uneven surface 41 as that during normal walking. Similar to these previous studies, our results also showed the similarity of the extracted muscle synergies between land and water walking at the same speed.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the task specificity of locomotor muscle synergies, although whether the number of muscle synergies during locomotion changes depending on speed is still controversial, the temporal activation coefficients are modulated depending on speed 15 , 19 22 . Other studies have reported that similar muscle synergies are used for walking on different slopes, but the activation combination across muscles and the temporal activation coefficients are modulated depending on the conditions 23 , 24 . To date, no study has investigated the muscle synergies used during underwater walking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, motor modules at different levels (often called synergies) have been revealed, thereby providing support for the modular control hypothesis [10]. For example, studies on the neural control of muscles show that a few muscle synergies sufficiently describe various muscle activation patterns in human locomotion [4,13,14]. Studies on kinematics find that the joint motions of the lower limb can be effectively explained by a few kinematic synergies in some typical human movements (e.g.…”
Section: Introductionmentioning
confidence: 87%
“…In healthy young adults, locomotor movements can be accommodated to various situations, such as walking slopes ( Hong et al, 2014a , b ; Dewolf et al, 2017 ) or stepping on stairs ( McFadyen and Winter, 1988 ; Silverman et al, 2014 ), by means of appropriate changes in the intersegmental coordination and muscle activations ( Dewolf et al, 2018 , 2020b ). During walking uphill and upstairs, the height of the center of mass of the body (COM) must be increased each step whereas it must be decreased during walking downhill and downstairs.…”
Section: Introductionmentioning
confidence: 99%